Integral assessment of urban conglomeration versus centre-periphery maglev rail systems under market imperfections - Jan Oosterhaven; Ward E. Romp; J. Paul Elhorst (European Regional Science Association (ERSA), 2002)
New transport infrastructure has a myriad of short and long run effects. The effects on population and economic activity are most difficult to estimate. This paper introduces three different models to estimate the impacts of new infrastructure on labour supply and demand, and carefully explains how the interaction between the models and their outcomes should be handled. A commuter location model is developed to estimate the impact of enabling longer commuting ranges within the same commuting time on housing migration. A spatial general equilibrium model (RAEM) is developed to estimate the impacts of increased spatial competition on firms and spatial production choices. The commuter location model is then used again to estimate the residential choices of the subsequent labour migration. Finally, an interregional commuter expenditure multiplier matrix is constructed to estimate the employment effects of both housing and labour migration. The methodology developed is applied to four Transrapid (magnetic levitation rail) proposals, each following a different route within the Netherlands. The empirical outcomes show remarkable patterns of effects and differences in effects, which were not expected beforehand but be explained quite well. Thus important new insights into the spatial pattern of indirect effects of new infrastructure in general are provided.
Keywords: 330